PENEGAKAN HUKUM E-TILANG: STUDI KASUS DI KOTA PEKANBARU TAHUN 2022-2023 - Hibatullah, Alfikri Udzri Ramadhan; ', Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The level of traffic violations in Indonesia is considered very high, especially in big cities such as Pekanbaru City. Along with the increasingly advanced development of technology and information, the Indonesian Police developed an information system supported by network or website-based software with the help of electronic equipment called electronic ticketing (E-Tilang)/ETLE. This aims to achieve a relevant ticketing process that enables the dissemination of information to every member of the police. The presence of this national electronic ticket is to improve public security and safety programs on the highway. National ETLE detects all vehicles, both two-wheeled and four-wheeled, that do not comply with traffic rules. The research method used is a qualitative approach with descriptive explanations. The types of data are primary data and secondary data. Primary data is obtained from the results of direct observation and interviews with someone (informant), while secondary data is data that supports or strengthens primary data. Data collection techniques through interviews and documentation. The data analysis technique used is the data collection technique from Miles and Huberman. The research results show that the implementation of electronic tickets for traffic violations in the jurisdiction of the Riau Regional Police through (ETLE) has not been optimal in dealing with traffic violations on the highway, because (ETLE) can only detect certain types of violations. Apart from that, the application of ETLE cannot be carried out on drivers or owners of motorized vehicles who do not confirm traffic violations involving vehicles detected by ETLE cameras either directly by visiting the ETLE Command Post or online so they cannot be subject to fines. ETLE also cannot take action against motorized vehicles that use vehicle registration numbers that do not match the motorized vehicle registration number registered with Samsat. Keywords: Implementation, ETLE, Violation.